2014
DOI: 10.1167/iovs.13-13732
|View full text |Cite
|
Sign up to set email alerts
|

Fullerenol Protects Retinal Pigment Epithelial Cells From Oxidative Stress–Induced Premature Senescence via Activating SIRT1

Abstract: Fullerenol could rescue RPE cells from oxidative stress-induced senescence through its antioxidation activity and the activation of SIRT1. The protective effect of Fol is useful for the development of new strategies to treat oxidative stress-related retinal diseases like AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 37 publications
4
43
0
Order By: Relevance
“…The agent was shown to induce apoptosis in such cancer cells as skin cancer cells, 35) colon cancer cells, 36) and neuroblastoma Cells, 37) whereas was indicated to exert the protective role against apoptosis in the human tenocytes, 38) in endothelial cells 39) and in other types of cells, 40) particularly, under the pressure of oxidative stress. [40][41][42] And in this study, we confirmed the protective role of RSV and the Sirt 1 activation against the H 2 O 2 -induced apoptosis in MC3T3-E1 osteoblast cells. Moreover, based on the above results, we speculated that activation of p53 acetylation by H 2 O 2 -induced downregulation of Sirt 1 could increase the Bax, whereas could reduce the Bcl-2, at protein level.…”
Section: Discussionsupporting
confidence: 80%
“…The agent was shown to induce apoptosis in such cancer cells as skin cancer cells, 35) colon cancer cells, 36) and neuroblastoma Cells, 37) whereas was indicated to exert the protective role against apoptosis in the human tenocytes, 38) in endothelial cells 39) and in other types of cells, 40) particularly, under the pressure of oxidative stress. [40][41][42] And in this study, we confirmed the protective role of RSV and the Sirt 1 activation against the H 2 O 2 -induced apoptosis in MC3T3-E1 osteoblast cells. Moreover, based on the above results, we speculated that activation of p53 acetylation by H 2 O 2 -induced downregulation of Sirt 1 could increase the Bax, whereas could reduce the Bcl-2, at protein level.…”
Section: Discussionsupporting
confidence: 80%
“…24,25) The whole cell extracts were incubated with 10 µL SIRT1 Substrate Solution in 96-well plates at 37°C for 30 min, and then mixed with Developing Solution at 37°C for 10 min. Meanwhile, the standard curve was determined.…”
Section: Methodsmentioning
confidence: 99%
“…23 We used Western blot analysis to evaluate acetyl-p53 expression at 24 and 48 h after TCDD exposure, to assess the possible role of H2 in suppressing cellular senescence. Total p53 expression in HUVECs did not significantly differ between normal and hydrogen-rich media or between media with and without TCDD (Figures 5A,B).…”
Section: Effects Of Hydrogen-rich Medium On P53 Acetylationmentioning
confidence: 99%
“…32, 33 Furthermore, activation of p53 by acetylation was found to be associated with cellular senescence caused by oxidative stress. 23 To examine further the effects of H2 on preventing cellular senescence, we assessed induction of acetyl-p53 in HUVECs treated with hydrogen-rich water. H2 significantly decreased induction of acetyl-p53 at 24 h after TCDD incubation.…”
Section: Effects Of Chrysin On H2-induced Changes In Huvecsmentioning
confidence: 99%